Real-word adrenocorticotropic hormone treatment for childhood-onset nephrotic syndrome - Wang, Ying; Dang, Xiqiang; Wu, Xiaochuan; Li, Yongzhen; He, Qingnan; Li, Xiaoyan (Frontiers in Pediatrics, 2023)
Background: Current first-line anti-proteinuric treatments do not produce a satisfactory therapeutic effect in a considerable number of patients with nephrotic syndrome (NS). Interest in adrenocorticotropic hormone (ACTH) for the treatment of NS has recently been revived. The present study investigated the efficacy and safety of ACTH treatment in children with frequent relapsing NS (FRNS), steroid-dependent NS (SDNS), and steroid-resistant NS (SRNS). Method: The ACTH treatment group was comprised of NS patients receiving ACTH treatment. Patients with serum cortisol concentrations <85.3 nmol/L and who had not received ACTH treatment previously were enrolled in the control group from January 2018 to January 2021. The maintenance dose of prednisone, the number of disease recurrences, the time of first disease relapse, immunosuppressant use, serum cortisol levels, and adverse events were recorded in both groups. Results: Fifty-one patients were included in the ACTH group, and twenty-one patients were enrolled in the control group. Concurrent treatment with one or more immunosuppressive and/or cytotoxic treatments occurred in 92.2% and 85.7% of patients in the ACTH and control groups, respectively, throughout the study period. A greater reduction in the prednisone maintenance dose was observed in the ACTH group compared with the control group after 1 year of follow up (0.603±0.445mg/kg vs. 0.267±0.500 mg/kg, p=0.006). During the one-year study period, fewer participants experienced one or more disease relapses in the ACTH group (45.1%) compared to the control group (76.2%, odds ratio=3.892, p=0.0016). The number of disease recurrences per patient in the ACTH group was less than that in the control group (median difference=-1, p=0.006). The mean length of remission was 8.902m and 7.905m in the ACTH group and control group, respectively. A log-rank test showed a longer relapse free survival for patients in the ACTH group (p=0.046), but the Breslow test showed no significant difference between groups (p=0.104). Ten patients in the ACTH group successfully discontinued all drug therapies. No patients in the control group were able to discontinue drug therapy as of February 2022. Conclusion: ACTH, combined with multiple drugs, is effective at reducing the prednisone maintenance dose and may effectively prevent disease relapses in childhood NS.